Richness and endemism in Chusquea subg. Swallenochloa (Poaceae), a Neotropical subgenus adapted to temperate conditions - Ruiz-Sanchez, Eduardo; Munguía-Lino, Guadalupe; Pianissola, Evandro Machado; Ely, Francisca; Clark, Lynn G. (Phytotaxa, 2023)
Chusquea subg. Swallenochloa comprises 52 species distributed in five biogeographical areas (Mexican Transition Zone, Brazilian subregion, South American Transition Zone, Chacoan subregion, and Andean region). Species of the subgenus grow from almost sea level in the Andean region to almost 4000 m in the northern South American Transition Zone (SATZ) and are often common or dominant elements of the vegetation. In this study, three questions related to species richness, endemism, and risk category of Chusquea subg. Swallenochloa were addressed. Analyses were based on the geo-referenced occurrence data of these 52 species, using different methods and software programs. Results indicate that the Chacoan subregion and SATZ had the highest richness with 16 and 15 species, respectively. The area of highest endemism was found in the Brazilian subregion. The AOO and EOO methods provided strongly differing estimations of conservation status.